The estimation of probability of the downtime of the vehicles under the changing conditions of the port industrial process - Корниец, Татьяна Евгеньевна (Technology audit and production reserves, 2015)
The estimation of the probability of downtime of the means of transport at varying conditions of port industrial process was suggested which affect the intensity and the time of processing vessel. The number of means of transport at the port terminal at a time and the number of efficient handling machines is referred under the productive process. The approach is based on the theory of queuing systems operating in a random environment. The case of direct interaction option of two transport streams were considered at one berth. To solve this problem the use of a special algorithm is provided, which is a combination of the probability of an asymptotic expansion in powers of a small parameter and matrix algorithm. The results allowed to formulate probabilistic indicators of port industrial process under varying conditions. The practical use of these parameters enables the management of a port terminal for more efficient process control and forecasting of possible economic losses caused by the decrease in the intensity of means of transport handling.